Implementasi Peraturan Daerah Kota Metro Tentang Penanggulangan Penyakit Sosial Masyarakat Terhadap Praktek Prostitusi Online Di Kota Metro - Salim, Choirul (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2020)
ABSTRACT The problem of prostitution is nothing new in Indonesian society, currently online-based prostitution is increasingly rampant. This phenomenon is a social problem because it involves social and moral values ​​in people's lives. This social problem cannot be overcome if there is no special attention from all parties, both government and society. From this, the authors are interested in conducting research related to the implementation of the Metro City Regional Regulation Number 07 of 2016 concerning Community Social Disease Management, especially the practice of online prostitution in Metro City. This research is a field research (Field Research) which describes the implementation, obstacles and solutions to the implementation of the Metro City Regional Regulation Number 07 of 2016 concerning Community Social Diseases Management of the practice of online prostitution in Metro City. Based on the results of the research, it can be concluded that the implementation of the Metro City Regional Regulation Number 7 of 2016 concerning Community Social Diseases Control regarding online prostitution has not been implemented optimally, Satpol PP officers who are in charge of local regulations have taken serious control but sanctions are given to disease perpetrators. social in the community only in the form of social guidance and sanctions. In the regional regulation Number 07 of 2016 concerning Community Social Diseases Management, it has not yet provided clear sanctions to perpetrators of social diseases such as online prostitution, because there are no implementing or guardian regulations regarding these regional regulations. Because the guardian's function explains the articles in regional regulations. The solution is that the local government must issue a guardian or implementing regulations from the Metro City Regional Regulation Number 07 of 2016 concerning Community Social Disease Management and need active participation of all components in tackling social diseases, especially those related to online prostitution. Keywords: Local Regulation, Implementation, Online prostitution